Prevalence, risk factors and quality of life in Turkish women with urinary incontinence: a synthesis of the literature. (26th July 2013) - Basak, T.; Kok, G.; Guvenc, G.
<x xml:space="preserve">Abstract</x> Background Urinary incontinence (UI) is not a life threatening condition but it adversely affects physical and mental health, sexual function and quality of life in women. Aim To review the related literature to identify prevalence, risk factors and quality of life among only Turkish women. Methods Computerized searches on PubMed, Turkish Medline, EBSCO Host; articles from indexed journals related to the topics in this review and published between 1996 and 30 April 2012 were evaluated. After completion of database searches, a final total of 20 studies were identified that fitted the inclusion criteria. Results This review revealed that the prevalence of UI among Turkish women was reported by 16 studies ranged from 16.4% to 49.7%. The most common risk factors were age, number of births, body mass index > 25 kg/m2, recurrent urinary infection, diabetes mellitus and vaginal delivery. The effect of UI on the quality of life was mild to moderate. Conclusions We found that the prevalence of UI of Turkish women showed a wide range. It is important for health professionals to be aware of the high prevalence of UI in women and to ask about its possible presence. Improving the quality of life in women with UI is an important issue and nurses should direct women to seek psychosocial support. The findings of this review could serve as a source of information for health systems that deal with UI, and it may help to inform health professionals and women with UI on early diagnosis, treatment and management.